Мотиви українського фольклору в контексті козацької тематики поем "Януш Бенявський" та "Дем'ян, князь Вишневецький" Юзефа Богдана Залеського - Білоцерківський, В. (Народна творчість та етнографія, 2007)
The article is devoted to the so-called “Cossack” poems “Janusz Bieniawski” and “Damian Ksiaże Wiśniowiecki” of the Polish romantic poet Jozef Bohdan Zaleski. In particular folklore motifs of the poems are analysed in the research.